Pengaruh Literasi Digital, Pemanfaatan Media Pembelajaran, dan Lingkungan Keluarga Terhadap Motivasi Belajar Siswa SMPN 01 Tanjungbumi Bangkalan Madura - Kholid; Nelud Darajatul Aliyah; Didit Darmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze and determine the influence of digital literacy on students' learning motivation at SMPN 01 Tanjungbumi Bangkalan Madura. This research uses a survey method and is quantitative in nature, with the results that the family environment, use of learning media, and digital literacy influence students' desire to learn. It can be concluded that these three factors are significant in determining it.